Determinating Variables Of Profitability And Return Of Islamic Stocks In Indonesia - Ahmad Roziq; Mar’atul Qibtiyah; Septarina Prita Dania S; Lely Ana Ferawati Ekaningsih (Jurnal Istiqro, 2021)
The research aims to analyze and prove the effect of solvability, liquidity, and activity toward profitability and return of Islamic stock in Indonesia. The researchers use explanatory research to explain the relationships between independent, intervening, and dependent variables. The data analysis technique uses the Path Analysis to examine direct and indirect impact variables of solvability, liquidity, and activity toward the return of Islamic stocks through profitability variable. This type of research is explanatory research which is research that explains the effect of independent variables on the dependent variable through a hypothesis test and uses path analysis. The researcher uses purposive sampling to determine the total sample of Islamic stocks indexed Jakarta Islamic Index. Secondary data used in this study are financial statement data and stock returns of companies listed on the Jakarta Islamic Index (JII) for the 2015-2019 period. . The results of the research found that (a) liquidity has no significant effect on profitability; (b) solvability has a significant effect on profitability; (c) activity has no significant effect on profitability; (d) liquidity has a significant effect on the return of Islamic stocks; (e) solvability has no significant effect on Islamic stocks; (f) activity has a significant effect on the return of Islamic stocks and ; (g) profitability has a significant effect on the return of Islamic stocks.